Quest for Conception: Gender, Infertility, and Egyptian Medical Traditions by Marcia C. lnhorn. University of Pennsylvania Press, 1994. (American Journal of Islam and Society, 1998)
Infertility is normally thought to be a problem for the rich, Western world,overpopulation the problem of the poor, Third World. But is this dichotomybuilt on empirical facts or on racial prejudices? Available statistics surprisinglyreveal an infertility belt from the Sudan and across Africa, where the problem incertain countries is extremely widespread. This and the AIDS epidemic threaten,according to Marcia lnhom, to depopulate large areas. In Egypt, official statisticsshow the infertility rate lo be 8%, a number Inborn regards as unrealisticallylow, but still it is eight times the number in Korea and Thailand. Despitesuch high figures, the focus in Egypt is only on hypofertility and family planning.Even so, the population is stilJ increasing due, says lnhom, to politicians'and health personnels' ignorance of the dialectic between fertility and infertility.lnhom goes a long way toward exposing the "overpopulation problem" as amyth. She takes as her starting point the U.N. declaration of human rights, whichasserts the right of all individuals to found a family, and transfers the focus tochildless Egyptians, which she claims is a muted group.Quest for Conception is the first comprehensive account of infertility in theThird World and represents a breakthrough in medical anthropology. Becausethis topic is highly gendered, the book also makes an important contribution togender studies. Her 100 childless informants from Alexandria are all poorMuslim women, and Quest for Conception can be read both as a study of povertyand of female Islamic practice.lnhom analyzes the extent of infertility, its causes and existing forms of treatment(both ethno- and biomedical), and potential reforms. Her material is basedon childless women's medical life stories-which often contain an astonishingvariety of treatments. In addition, she has followed them through 15 months ofdesperate search for children (1988-89). In all this time, only one(!) succeededin giving birth. The others presumably are continuing their restless search for thechild they need in order to realize their one and only career-motherhood. Thewomen's own experiences and emotional reactions, their subjective understandingof causes and different methods of treatment, and their strategies are centralto lnhom's very humane ethnography. But this micromaterial is continuously ...